STUDI HADIS TENTANG BERPEGANG TEGUH PADA AL-QUR’AN DAN ‘ITRAH AHLUL BAIT (KAJIAN TEMATIK) - Yasrizal Yasrizal; Nurlizam Nurlizam (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research is motivated by the author's interest in the low and minimal knowledge of some Muslim communities regarding the ahlul bait, some even criticize and insult the ahlul bait of the Prophet SAW. The aim of this research is to analyze the quality and understanding of the hadith regarding 'Itrah ahlul bait and who the actual ahlul bait are. So that it can answer problems that occur in the Muslim community regarding doubts about the nasab of the ahlul bait. This research is qualitative research, with data analysis techniques using the Maudhu'i method or thematic study, tools from hadith books and hadith sharia. And there are still many books and scientific works that are used to find answers to the problems contained in this research. The results of this research reveal that what is meant by the hadith of sticking to the Qur'an and 'Itrah ahlul bait is ahlul bait who are always awake and carry out the sunnah of the Prophet Muhammad, and are based on the Qur'an and Hadith in every action, and why the Prophet recommending the members of the temple because they are a family that has always been guided by the Prophet to always have faith and obey and act fairly with the teachings brought by the Prophet and the successors of his missionary work. And in another hadith which is the same as the discussion of this research, Rasulullah Saw explained that those included in his ahlul bait were, Fatimah, Ali, Hasan, and Husein. As well as his wives. And as for the explanation of the scholars regarding this hadith, not only those from the nuclear family are included in the ahlul bait group, but their uncles and their descendants are also included in the ahlul bait group. So it is not necessary for us Muslims to still be concerned about the fate of the current ahlul bait because they are still classified as ahlul bait.